Investigation of possible solubility and dissolution advantages of cocrystals, I: Aqueous solubility and dissolution rates of ketoconazole and its cocrystals as functions of pH - Jaydip M. Vasoya; Ankita V. Shah; Abu T.M. Serajuddin (ADMET and DMPK, 2019)
Since there are conflicting reports in the literature on solubility and dissolution advantages of cocrystals over free forms, we systematically studied solubility and intrinsic dissolution rates of a weakly basic drug, ketoconazole, and its cocrystals with fumaric acid and succinic acid as functions of pH to determine what advantages cocrystals provide. pH-solubility profiles were determined in two different ways: one by lowering pH of ketoconazole aqueous suspensions using HCl, fumaric acid and succinic acid, and the other by adjusting pH of cocrystal suspensions using respective coformer acids or NaOH. Similar pH-solubility profiles were obtained whether free base or cocrystals were used as starting materials to determine solubility. With the addition of fumaric and succinic acids to aqueous suspensions of free base to lower pH, the maximum solubility (pHmax) was reached at pH ~3.5-4.0, below which the solubility decreased and cocrystals formed. The solubility, however, continued increasing when HCl was added to ketoconazole suspension as no cocrystal or salt was formed. During determination of cocrystal solubility, a conversion to free base was observed when pH was raised above pHmax. Thus, pH-solubility profiles of cocrystals resembled solubility profiles commonly encountered with salts. Above pHmax, both free base and cocrystal had similar solubility under identical pH conditions; the solubility of cocrystal was higher only if the pH differed. In contrast, intrinsic dissolution rates of cocrystals at pH>pHmax under identical bulk pH were much higher than that of free ketoconazole since cocrystals had lower microenvironmental pH at the dissolving surface, where the solubility was high. Thus, cocrystals of basic drugs can potentially provide higher dissolution rates under intestinal pH conditions.